Study on acoustic emission characteristics under compression and fractal dimension of pore structure of polyvinyl alcohol fiber engineered cementitious composites - Li, Yueqiang; Huang, Xin; Zhao, Yangcan; Qiao, Yanyang (Frontiers in Materials, 2024)
Fiber adding to engineered cementitious composites (ECC) can effectively improve the performance of material. This study used the acoustic emission (AE) technique to study the influence of polyvinyl alcohol (PVA) fibre content on compressive strength and damage evolution of ECC and used the fractal theory to analyse the pore structure of PVA-ECC, which innovatively explored the mechanical properties and durability of PVA-ECC from macro and micro perspectives. In terms of mechanical properties, the compressive strength of ECC with 1% PVA volume content was the highest. PVA changed the compression damage mechanism of ECC, showing a decrease in internal tensile cracking and an increase in shear cracking through RA-AF values. ECC developed from brittle damage to ductile damage. In terms of microstructure and durability, ECC with 1% PVA volume content had the best impermeability and pore structure fractal characteristics, and PVA had a great influence on the fractal characteristics of transition pores and capillary pores. The fractal dimension had a good correlation with porosity, total pore volume, most probable aperture, compressive strength and chloride diffusion coefficient, indicating that the mechanical strength and impermeability of ECC were closely related to the complex spatial structure and distribution characteristics of pores. The fractal dimension can be used to comprehensively characterise the mechanical properties and durability of ECC.